The Role of Resistance Genes in Antibiotic Resistance (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
Antibiotic resistance has become one of the most serious global public health challenges. The excessive and inappropriate use of antibiotics has accelerated the emergence of resistant bacteria, making many infections difficult to treat. Bacteria develop resistance through several mechanisms, including enzymatic inactivation of antibiotics, modification of target sites, reduced drug permeability, and active efflux pumps. Resistance genes can spread rapidly between bacteria by horizontal gene transfer, increasing the prevalence of multidrug-resistant pathogens. Understanding these resistance mechanisms is essential for developing new antimicrobial agents and improving treatment strategies. Effective antibiotic stewardship, infection prevention, surveillance of resistance genes, and research into novel therapeutic approaches are necessary to slow the spread of antimicrobial resistance (AMR). Continued global collaboration among healthcare professionals, researchers, and policymakers is crucial to preserve the effectiveness of existing antibiotics and protect public health for future generations.
Keywords: Antibiotic resistance; Antimicrobial resistance (AMR); Bacteria; Resistance genes; Multidrug resistance (MDR); Antibiotics; Efflux pumps; Horizontal gene transfer